The Effect of Perceived Ease of Use on User Interest in the ShopeePay Digital Wallet among Generation Z in Surabaya - Safitri, Annisya Dellia; Zawawi, Zawawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to find out how Generation Z in Surabaya is influenced by the perception of ease of use of the Shopeepay digital wallet and the promotion of cashback vouchers to their interest in using it. Quantitative methods are used in this study. Since the size of the population cannot be determined with certainty, the method of sample selection is based on the guidelines for measuring the sample by specifying parameters. 96 respondents who are Generation Z and ShopeePay digital wallet users in the city of Surabaya were given a questionnaire as part of the data collection process. Structural Equation Modeling (SEM) based on variance is then used to analyze the data obtained. Partial Least Square (PLS SEM) software is used in this technique, which is also referred to as the alternative SEM method. The results of this study show that generation Z in the city of Surabaya is significantly more interested in using the ShopeePay digital wallet because it is considered easy to use and offers cashback vouchers."